Salidroside protects against homocysteine‐induced injury in human umbilical vein endothelial cells via the regulation of endoplasmic reticulum stress. Issue 1 (February 2017) - Zhu, Lin; Jia, Fang; Wei, Jiang; Yu, Yang; Yu, Tianhong; Wang, Yanjun; Sun, Jianhui; Luo, Guanghua
Summary: Introduction: Previous studies showed that homocysteine (Hcy) could injure vascular endothelial cells via several mechanisms, including its promotion of oxidative stress pathway and endoplasmic reticulum stress (ER stress) pathway. Salidroside (SAL) is an active component of Rhodiola rosea with documented antioxidative properties. Emerging evidence conformed that SAL attenuated Hcy‐induced endothelial dysfunction by reducing oxidative stress. However, its role in ER stress pathway remains unclarified. Aims: The purpose of this study was to explore the mechanism of the protective effect of SAL on Hcy‐induced endothelial dysfunction. Results: Pretreatment of the human umbilical vein endothelial cells (HUVECs) with SAL significantly reduced the cell damage effects brought by Hcy in a dose‐dependent manner. Functional studies on the HUVECs found that SAL rescued the endoplasmic reticulum stress induced by Hcy. The underlying mechanisms involve the inhibition of Hcy‐induced activation of binding protein (Bip) and C/EBP homologous protein (CHOP), as well as the phosphorylation of protein kinase RNA‐like ER kinase (PERK) or inositol‐requiring enzyme 1 alpha (IRE1α). Conclusions: Taken together, these findings implicate that SAL could regulate ER stress pathway on the viability of endotheliocyte induced by Hcy in vitro. Our findings provide the first evidence that SAL plays an important role in endotheliocyte protection via suppressing ER stress pathway in HUVEC cells and that it may be a promising therapeutic target for atherosclerosis and cardiovascular disease.